Effect of Dietary Supplementation of Moringa oleifera Leaf Meal on Production and Reproduction in Rhode Island Red Chicken - D.G. Vaghamashi; D. D. Garg; G. P. Sabapara; K. B. Vala; J. A. Chavda; D. N. Borkhatariya; V. V. Gamit; H. P. Vijyeta (Indian Journal of Animal Nutrition, 2026)
A study was carried out to determine the effect Moringa oleifera leaf meal (MOLM) on production performance, semen quality, fertility, hatchability and chick quality of Rhode Island Red (RIR) chickens. One hundred and eighty, 24-week-old Rhode Island Red layer birds were randomly allotted to four dietary treatments having replicates with 15 birds in each. The treatments were T1 (Control: Basal diet); T2: 1% MOLM in basal diet; T3: 3% MOLM in basal diet; T4: 5% MOLM in basal diet. To study reproductive performance, 24 cocks at the age of 24th weeks were kept separately and equally divided into four groups and were provided same dietary treatments as provided to hens. The results revealed that average daily feed intake per bird (g/day) was lower (P<0.05) for hens supplemented with MOLM. No statistical difference for feed conversion ratio (FCR) was observed between groups. The average HDEP % and HHEP % of experiment were significantly (P<0.05) higher in T3 and T4 groups as compared to T1. The MOLM diet resulted in significantly (P<0.05) increased semen concentration, total sperm count, motility and live sperm than the control, however semen volume and pH were not differed between groups. Fertility % was linearly increased with MOLM but it was not statistically different (P>0.05) with control group. Hatchability percentage was higher (P>0.05) in T3 and T4 than the others. Hens in T2, T3 and T4 groups had higher mean values for average chick weight and chick length (P<0.05) than the control group. Results of the present study indicated positive response of Moringa oleifera leaf meal on production and reproduction performance when used in the diet of birds.